OWNERSHIP STRUCTURE AND FINANCIAL PERFORMANCE: EVIDENCE FROM EMERGING COMPANIES - Rahaman, Mohammed Ashiqur; Khan, Maksudur Momin; Chowdhury, Kanta; Masum, Mofijul Hoq (Research In Management and Accounting (RIMA), 2025)
The purpose of this study is to explore the impact of ownership structure on corporate performance from the context of an emerging country, Bangladesh. This empirical study is based on a dataset of 200 observations from the annual reports of twenty Dhaka Stock Exchange (DSE) listed pharmaceutical and chemical companies from the tenures of 2013 to 2022. Here a multiple regression model has been executed to explore the influence of ownership attributes on financial performance. It is found that director ownership, institutional ownership, general ownership and foreign ownership significantly influence the corporate performance. These findings imply the current comprehension of ownership structure and its association with financial success. This study also provides valuable insight for businesses and management to set their long-term vision and goals in terms of ownership and equity matters. External financiers and legislators can also benefit from this study in making investment decisions and new policies. Future researchers can expand their study reach by including more years of data, other relevant variables from the ownership structure field, macroeconomic variables, and other industries to serve the needs of a wide range of users.